Direct Detection of KPC Peak from Positive Blood Cultures Using MALDI-TOF MS: Are We There Yet? - Natália Kehl Moreira; Camila Mörschbächer Wilhelm; Aymê Duarte Echevarria; Fabiana Caroline Zempulski Volpato; Priscila Lamb Wink; Afonso Luís Barth; Juliana Caierão (Antibiotics, 2023)
Detecting carbapenemase-associated carbapenem resistance is a subject of major clinical and epidemiological concern as it influences therapeutic choice. Matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) has been proposed as a means to assess bacterial resistance mechanisms. We aimed to detect the KPC enzyme directly from positive blood cultures using MALDI-TOF MS. To do so, 102 clinical Enterobacteria were evaluated, including 59 blaKPC positives. Proteins were extracted using formic acid, isopropyl alcohol, and water (17:33:50) and spotted onto a steel target plate using the double-layer sinapinic acid technique. Two parameters were considered: (i) the visual detection of a clear peak with the expected KPC m/z and (ii) the evaluation of the relative intensity of the ions in the peak. A peak was observed in 56/59 blaKPC-positive isolates (94.9% sensitivity), with no false-positive results (100% specificity). When considering intensity, with a cut-off ≥120 (a.u.), sensitivity was 94.9% and specificity was 95.3%. We proposed a “buffer” zone, with intermediate values of intensity (115 to 125) reaching 100% sensitivity and specificity. The detection of KPC peaks directly from positive blood cultures using MALDI-TOF MS is feasible and rapid, which may improve appropriate patient therapy and antimicrobial stewardship.